The (in)visibility of translation and translators in the Swedish publication of post-Soviet Russian literature - Malin Podlevskikh Carlström (Stridon, 2022)
In this article the (in)visibility of translation and translators in Sweden is studied, based on the analysis of a corpus of 82 post-Soviet Russian novels. The aim is to investigate how (if at all) the peritexts reveal the foreign nature of the text and the identity of the translator. The analysis shows that the translator is rather invisible in the external peritext, which is placed on the cover or dust jacket of the published translation, while the foreign (and consequently also the translated) nature of the novel is highlighted. The translator’s visibility inside Swedish translations of post-Soviet novels is usually signaled on the title page. Apart from this, the translator is invisible. A few translator’s comments and notes are included in the translation, but usually these are inconspicuous and not explicitly attributed to the translator. Moreover, they are written in an apologetic tone and do not seem to wish to disturb the reader.